Effect of Nordic walking on walking ability in patients with peripheral arterial disease: a meta-analysis - Zerong Sun; Jing Zhang; Yiqun Fang; Yongdong Qian (PLoS ONE, 2025)
Background Evaluating the effectiveness of Nordic walking in influencing walking ability in patients with peripheral arterial disease. Methods We searched 12 databases, including PubMed, Embase, Cochrane library, Web of Science, EBSCO host, Ovid, Scopus, ClinicalTrial.gov, and several top ranked Chinese databases, including China National Knowledge Infrastructure (CNKI), Wanfang Data, CBMdisc, VIP Database, ChiCTR. The search has no starting time limit and the deadline is April 9, 2024. Randomized controlled trials and pseudo-random controlled trials were included. The two authors independently screened the literature and evaluated the quality of the study using the Cochrane risk of bias tool. Meta analysis was conducted using Review Manager 5.4 and Stata 17.0 software. Results A total of 8 studies involving 508 patients were included. Meta-analysis results showed that compared with supervised exercise therapy (SET), supervised NW was not associated with an increase in maximum walking distance (MWD) and claudication distance (CD) in PAD patients, whether during treadmill tests or 6-minute walk tests (6-MWT), and the results were not statistically significant. In terms of increasing exercise duration, SET was significantly higher than supervised NW and the results were statistically significant (SMD =  -0.41, 95% Cl: -0.72 to -0.09, Z =  2.54, P =  0.01 <  0.05). Among the 8 studies included, 2 studies had control groups that were not part of the supervised exercise program and were different, therefore no meta-analysis was conducted. Conclusions In PAD patients, supervised NW is no significant difference in walking ability compared to SET. NW presents a viable option when SET is not available. PROSPERO registration PROSPERO registration number: CRD42024535828